Analisis Perbandingan Harga Saham PT. Bank Syariah Indonesia Tbk Sebelum dan Sesudah Merger - Ramadhan, Bayu (Rifa'Institute, 2022)
Merger is one of the business processes that can increase asset capitalization and improve the Company's financial performance. On 1 February 2021, 3 State-Owned Sharia Banks were merged among PT BRI Syariah, PT Mandiri Syariah and PT BNI Syariah. Merger is a business strategy carried out between the 3 Sharia Banks in order to improve financial performance. The purpose of the research is to compare analysis before and after the merger of PT Bank Syariah Indonesia by comparing the average price of this company's stocks in the period 30 days before and 30 days after the bank merger. The effective date of the merger of the 3 BUMN Syariah Banks is 1 February 2021. The research method is a quantitative approach with comparative descriptive research by comparing the stock prices of PT. Bank Syariah Indonesia Tbk. in the period of before and after the merger. The Stock Price of PT Bank Syariah Indonesia Tbk. taken from the Google Finance website is the daily closing price data for the period 30 days before and 30 days after the merger date of PT. Bank Syariah Indonesia Tbk, which is 1 February 2021. The results showed that there was a significant increase, where the average share price of PT. Bank Syariah Indonesia Tbk. before the merger of IDR 1,785.38 increased to IDR 2,067.19 after the merger. The implementation of the merger at Bank Syariah Mandiri, BRI Syariah and BNI Syariah had a positive impact on financial performance as evidenced by the increase in share prices after the merger process of PT. Bank Syariah Indonesia Tbk